Compendium to the Primer for Space Cooling - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2020)
This compendium presents examples and analyses of space cooling interventions from across the world (from both developed and developing countries), with an aim to highlight the key insights learned. Interventions discussed in the compendium are meant to be options to inform strategies, implementation mechanisms, and road maps for countries that are seeking to address and increase sustainable space cooling. Interventions involve a combination of actions reducing cooling loads, serving cooling needs efficiently, and optimizing and controlling cooling loads. While each country will chart its own pathway toward sustainable space cooling, the need for a multipronged approach consistently applies. The best outcomes will emerge from a multipronged approach that incorporates information, policy and regulatory measures, clear leadership, financing and implementation models, training, and research and development. The objectives of the primer are to introduce a broad audience, including practitioners in different fields, to space cooling and to help initiate and advance sustainable space cooling into policy discussions and investment considerations in developing countries. The primer explains the foundational aspects of space cooling, makes the case that sustainable space cooling achieved through low-energy and low-climate-impact pathways is a critical priority, and emphasizes an integrative approach as essential to addressing space cooling sustainably.